A strategy for efficient enrichment of steroidal alkaloids from Fritillaria based on fluorinated reversed‐phase stationary phase. Issue 18 (6th August 2021) - Si, Wei; Yu, Dongping; Zhou, Han; Guo, Zhimou; Lu, Shubin; Peng, Ting; Liu, Yanming; Shen, Aijin; Liu, Yanfang; Liang, Xinmiao
Abstract: Plant‐derived alkaloids are bioactive natural ingredients, but their contents are relatively low in plants. Therefore, the efficient enrichment of alkaloids is a prerequisite for purification and further pharmacological research. In this study, an efficient and simple strategy for enrichment of steroidal alkaloids in Fritillaria was developed for the first time based on the fluorinated reverse‐phase stationary phase (FC8HL). Superior selectivity between alkaloids and non‐alkaloids was achieved in a non‐aqueous system, and a simple solvent system containing low‐content additives was applied to elute alkaloids. Key parameters that affected the elution were investigated, including different types of buffer salts and optimized concentrations. The optimized elution system was then applied to selectively enrich alkaloids from five species of Fritillaria. Its practicability was further demonstrated by enrichment of alkaloids from Fritillaria cirrhosa D.Don at a preparative level. This developed method has great potential for other types of hydrophobic alkaloids.